Revision of the genus Dilophus Meigen, 1803 (Diptera, Bibionidae) from the Afrotropical Ecozone - Skartveit, John; Freidberg, Amnon (Zootaxa, 2023)
We revise the Afrotropical species of the genus Dilophus Meigen, redescribing each species. Previous Afrotropical records of the Palaearctic species Dilophus antipedalis Wiedemann and Dilophus femoratus Meigen are found to be erroneous, both these represent undescribed species, the former is distributed in the mountains along the southern Rift Valley and described as Dilophus riftensis sp.n., specimens recorded as the latter from Madagascar is described as Dilophus malagasicus sp.n.. Furthermore, one montane or alpine species apparently endemic to Ethiopia is described, Dilophus baleensis sp.n.. Philia splendens Hardy, 1951 is found to be a junior synonym of Dilophus bicolor Wiedemann, 1821. We summarise what is known about the distribution and phenology of these species in the Afrotropical ecozone.